2016
DOI: 10.1021/acs.chemmater.6b01726
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Sequential Reversible Phase Transitions Containing Switchable Dielectric Behaviors in Cyclopentyl Ammonium 18-Crown-6 Perchlorate

Abstract: Multisequential reversible phase transitions based on molecular materials have important applications in ferroelastic materials, ferroeletric materials, switchable dielectric materials, and temperature-controlling materials. Here, we report that a new compound, [Hcpa-(18-crown-6)] + [ClO 4 ] − (1) (where Hcpa represents protonated cyclopentylamine cations) displays unusual multisequential reversible phase transitions accompanied by switchable dielectric behaviors. The stepwise synergistic disordering of Hcpa c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
76
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 32 publications
2
76
0
Order By: Relevance
“…This is because a ferroelectric is required to satisfy some specic conditions: (i) their lower symmetrical structures must fall into one of the 10 noncentrosymmetric and polar space groups (1, 2, m, mm2, 3, 3m, 4, 4mm, 6 and 6mm), 21 and (ii) the dipole moments that can generate remnant spontaneous polarization should exist in the ferroelectric structures. [22][23][24][25][26][27][28] However, in a molecular system with reversible phase transitions, if we x a body part that can afford the "driving/controlling force" of the structural transition and carry out certain structural modications to create polarization, can we design and construct a new ferroelectric through this molecular system? Ferrocene, the rst reported sandwich complex, possesses two typical reversible structures, the overlapping (D 5h ) and interlaced (D 5d ) cyclopentadienyl rings (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…This is because a ferroelectric is required to satisfy some specic conditions: (i) their lower symmetrical structures must fall into one of the 10 noncentrosymmetric and polar space groups (1, 2, m, mm2, 3, 3m, 4, 4mm, 6 and 6mm), 21 and (ii) the dipole moments that can generate remnant spontaneous polarization should exist in the ferroelectric structures. [22][23][24][25][26][27][28] However, in a molecular system with reversible phase transitions, if we x a body part that can afford the "driving/controlling force" of the structural transition and carry out certain structural modications to create polarization, can we design and construct a new ferroelectric through this molecular system? Ferrocene, the rst reported sandwich complex, possesses two typical reversible structures, the overlapping (D 5h ) and interlaced (D 5d ) cyclopentadienyl rings (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…A reversible SCSC phase transition can occur when the changes in the molecular conformation and packing arrangement in the crystal are very small at the phase transition, so there are no cracks or breaks in the crystal. Hence, the reversible SCSC phase transition is a fascinating phenomenon because of its potential applications in ferroelectric and switchable dielectric devices [1][2][3]. Several molecular crystals that undergo temperature-induced reversible SCSC phase transition have been reported [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[22] Du et al also reported ac oordinated water molecule in the (tBuNH 3 )(18-crown-6)[ZnCl 3 (H 2 O)],w hich undergoes as light polar rotation. [23] Our groups have previously synthesized an inclusion compound, cyclohexyl ammonium1 8crown-6 tetrafluoroborate (or perchlorate), [24] [Hcha-(18-crown-6)] + [BF 4 ] À and[ Hcha-(18-crown-6)] + [ClO 4 ] À (Hcha = protonated cyclohexyl ammonium), [20] in which the protonated cyclohexylamine cationsu ndergo pendulum motion for the high temperature para-ferroelectric phase transition.…”
Section: Introductionmentioning
confidence: 99%